2007
DOI: 10.1111/j.1526-100x.2007.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Regeneration: Lessons from a Degraded Grassland

Abstract: To gain insight into mechanisms controlling ecosystem regeneration, we investigated a grassland that was heavily polluted by a phosphate fertilizer factory between 1960 and 1990. Abiotic and biotic filters that influenced species assemblage and succession were monitored and restoration approaches assessed. Studies included the investigation of soil parameters, impact of abiotic stress on microbes and plants, plant succession, recolonization mechanisms, functional group interactions, mycorrhizal diversity and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…While the addition of mineral fertilizer only increases nutrient availability, the addition of organic fertilizer can also increase ion-exchange capacity (reducing nutrient leaching) and water retention capacity (Johnson, 1987;Elmarsdottir et al, 2003). Regeneration of indigenous plant cover can also be inhibited by factors common to all regions, including the absence of viable seeds (Ebersole, 1989;Forbes and Jefferies, 1999;Prach et al, 2001) or of mycorrhizal inoculum (Greipsson and El-Mayas, 1999;Blanke et al, 2007), herbivory (Arnalds, 1987;Bradshaw, 1987), substrate instability (Walker and Del Moral, 2003), compaction (Billings, 1987), desiccation (Arnalds, 1987;Cargill and Chapin, 1987;Chapin, 1993), and low nutrient availability (Arnalds, 1987;Bradshaw, 1987;Blanke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While the addition of mineral fertilizer only increases nutrient availability, the addition of organic fertilizer can also increase ion-exchange capacity (reducing nutrient leaching) and water retention capacity (Johnson, 1987;Elmarsdottir et al, 2003). Regeneration of indigenous plant cover can also be inhibited by factors common to all regions, including the absence of viable seeds (Ebersole, 1989;Forbes and Jefferies, 1999;Prach et al, 2001) or of mycorrhizal inoculum (Greipsson and El-Mayas, 1999;Blanke et al, 2007), herbivory (Arnalds, 1987;Bradshaw, 1987), substrate instability (Walker and Del Moral, 2003), compaction (Billings, 1987), desiccation (Arnalds, 1987;Cargill and Chapin, 1987;Chapin, 1993), and low nutrient availability (Arnalds, 1987;Bradshaw, 1987;Blanke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Then, scores for the productivity of plants were correlated and, hence, shown that more diverse plant communities are more productive (Tilman et al 1996). Another study inspects soil parameters using statistics and simulation with respect to plant succession, recolonization mechanisms, functional group interactions, mycorrhizal diversity and function, and food web analysis (Blanke et al 2007). Such statistical methods are only possible for very small data sets, both in the number of examples and features.…”
Section: Environmental Approachesmentioning
confidence: 99%
“…Por tanto, la conclusión es obvia: se ha de poner el énfasis en la mejora de la gestión de los recursos forestales cuando se afronta la tarea de recuperar la cubierta forestal del sitio que sea (Blanke et al, 2007). Un ejemplo que puede ser representativo de la ausencia de una óptima gestión ambiental son las escasas labores de conservación que se estuvieron llevando a cabo en el delta del Llobregat.…”
Section: 3323-causas Por Las Cuales Se Produce La Fragmentación De Los Bosquesunclassified